Analysis of Human Resource Readiness in the Implementation of the Central Health Management Information System (SIMPUS) and the Integrated Referral Information System (SISRUTE) - Hemma, Helmiati; Gaffar, Herry Darsim; Patarai, Muhammad Idris (Universitas Mandala Waluya, 2025)
Digital transformation in Indonesia's health sector through the implementation of SIMPUS and SISRUTE aims to improve the quality of health services and operational efficiency. SIMPUS is designed to integrate various operational functions of community health centers, while SISRUTE connects patient referral processes between health facilities. These two systems also strengthen coordination between health agencies. This study analyzes the readiness of human resources in the implementation of SIMPUS and SISRUTE using an associative quantitative design, a cross-sectional study approach, and ordinal regression tests. The research sample consisted of 39 respondents selected through total sampling. The results of the analysis show that technical competence and skills (p = 0.025), training and capacity building (p = 0.011), attitudes and perceptions (p = 0.018), mental readiness (p = 0.029), and performance and productivity (p = 0.015) significantly affect human resource readiness in the implementation of SIMPUS and SISRUTE. The conclusion of this study confirms that improving competence, continuous training, strengthening positive attitudes, mental readiness, and better performance are key factors in ensuring the effective and successful implementation of SIMPUS and SISRUTE, as well as improving the quality of health services in Community Health Centers and Hospitals.